Seroepidemiology of pertussis and diphtheria among healthy adults in Shaanxi Province, northwest China: A large - scale cross-sectional study - Chao Zhang; Weijun Hu; Ruize Wang; Yinan Wang; Yajun Li; Yake Lv; Weixuan Li; Yuan Si; Shaobai Zhang (Taylor & Francis Group, 2022)
To determine the estimated pertussis incidence in adults and the need for a booster dose by detecting pertussis and diphtheria antibody levels in adults in Shaanxi province, China. Blood samples were collected from healthy individuals aged 18-59 years in Shaanxi province in 2017. Serum immunoglobulin G (IgG) antibodies against pertussis toxin (PT) and diphtheria toxin (DT) were determined using enzyme-linked immunosorbent assay. The data on reported pertussis cases in Shaanxi province were collected from the China Information System for Disease Control and Prevention and compared with the results of this study. A total of 4307 subjects were enrolled. The mean concentration of anti-PT IgG was 19.6 IU/mL (95% CI = 18.9-20.3), and the positive rate (≥40 IU/mL) was 11.0% (474/4307), of which recent infections (≥100 IU/mL) accounted for 1.2% (53/4307). Only one adult case of pertussis was reported in 2017, which is much lower than the results of this study. The mean concentration of anti-DT IgG was 0.04 IU/mL (95% CI = 0.04-0.05), and the positive rate (≥0.01 IU/mL) was 82.3% (3543/4307). The mean concentration of anti-DT IgG decreased from 0.07 IU/mL in the 18-29 year-old group to 0.03 IU/mL in the 50-59 year-old-group, and the positivity rate decreased from 86.7% to 78.7%. Our study suggests that pertussis is not uncommon among adults. The existing surveillance system might have underestimated the true incidence of pertussis. The diphtheria antibody levels decreased with age. Booster vaccination against pertussis should be considered for adolescents and young adults.